2010
DOI: 10.1088/1468-6996/11/5/054602
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free phthalocyanine (H2Pc) molecule adsorbed on the Au(111) surface: formation of a wide domain along a single lattice direction

Abstract: Using low-temperature scanning tunneling microscopy (STM), we observed the bonding configuration of the metal-free phthalocyanine (H 2 Pc) molecule adsorbed on the Au(111) surface. A local lattice formation started from a quasi-square lattice aligned to the close-packed directions of the Au(111) surface. Although we expected the lattice alignment to be equally distributed along the three crystallographically equivalent directions, the domain aligned normal to the ridge of the herringbone structure was missing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…1a ) was synthesized according to the previously reported procedures 22 . The molecule was transferred to a Au(111) substrate using a sublimation method under ultra-high vacuum conditions, by heating the sample in a Ta boat at ∼300 °C (refs 23 , 24 ). During the sublimation process, Cu-BCOD was converted into the Cu-Benzo molecule via a retro-Diels–Alder reaction involving the extrusion of four ethylene molecules from the fused BCOD rings as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a ) was synthesized according to the previously reported procedures 22 . The molecule was transferred to a Au(111) substrate using a sublimation method under ultra-high vacuum conditions, by heating the sample in a Ta boat at ∼300 °C (refs 23 , 24 ). During the sublimation process, Cu-BCOD was converted into the Cu-Benzo molecule via a retro-Diels–Alder reaction involving the extrusion of four ethylene molecules from the fused BCOD rings as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…10, 11 Mazur et al 12 studied the spectroscopy and resonant tunneling in different metal phthalocyanines. Komdea 13 showed that the orientation of individual H 2 Pc molecules adsorbed on Au(111) is surface driven. Cheng and co-workers 14 proposed that FePc adsorption on Au(111) is controlled by molecule− molecule interactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[77][78][79][80][81][82][83][84] Here we discuss the case of H 2 Pc on Au(111) surfaces. [85] An STM image of a scattered H 2 Pc molecule on an Au(111) surface obtained at a sample T of 4.7 K is illustrated in Figure 12a. The cross-like protrusions correspond to H 2 Pc molecules.…”
Section: Bonding Configuration Of Pc Moleculementioning
confidence: 99%
“…One of the two symmetry lines of a molecule is aligned to the close-packed directions of the substrate (A1, A2, or C in Figure 12b), so as to gain larger van der Waals interaction energy due to a larger overlap between the molecule and the substrate. [85] An STM image of a monolayer film of H 2 Pc molecules is shown in Figure 12c. An ordered array of molecules can be seen, together with long-range undulation, reflecting the herring-bone structure of Au (111).…”
Section: Bonding Configuration Of Pc Moleculementioning
confidence: 99%
See 1 more Smart Citation